Are we nearly there yet? A study of the English National Health Service as professional bureaucracies. Issue 4 (19th June 2017) - Dickinson, Helen; Snelling, Iain; Ham, Chris; Spurgeon, Peter C.
Abstract : Purpose: The purpose of this paper is to explore issues of medical engagement in the management and leadership of health services in the English National Health Service (NHS). The literature suggests that this is an important component of high performing health systems, although the NHS has traditionally struggled to engage doctors and has been characterised as a professional bureaucracy. This study explored the ways in which health care organisations structure and operate medical leadership processes to assess the degree to which professional bureaucracies still exist in the English NHS. Design/methodology/approach: Drawing on the qualitative component of a research into medical leadership in nine case study sites, this paper reports on findings from over 150 interviews with doctors, general managers and nurses. In doing so, the authors focus specifically on the operation of medical leadership in nine different NHS hospitals. Findings: Concerted attention has been focussed on medical leadership and this has led to significant changes to organisational structures and the recruitment and training processes of doctors for leadership roles. There is a cadre of doctors that are substantially more engaged in the leadership of their organisations than previous research has found. Yet, this engagement has tended to only involve a small section of the overall medical workforce in practice, raising questions about the nature of medical engagement more broadly. Originality/value: There are only a limited number of studies that have sought to explore issues of medical leadership on this scale in the English context. This represents the first significant study of this kind in over a decade.